The Issue of Poland’s Dependence on Natural Gas Supplies from the Russian Federation in the Political Thought of Piotr Naimski: Selected Problems - Paszkowski, Michał (Historia i Polityka, 2022)
The topic of the research was the political thought of Piotr Naimski in the field of reducing Poland’s dependence on natural gas supplies from the Russian Federation. The aim of the article was therefore to analyse Naimski’s views on the diversification of the sources and directions of natural gas supplies to Poland and to define the political concepts formulated by this politician. The article indicates Naimski’s views on increasing Poland’s energy security by realizing energy projects such as LNG terminal, Baltic Pipe gas pipeline, as well as activities aimed at counteracting the Russian Federation energy policy in Central Europe. Naimski was one of the staunchest opponents of the construction of Russian-German gas pipelines (Nord Stream and Nord Stream 2).